Mathematical Modeling Applied to Burn Injuries - Devkota, Jyoti U.; Saxena, V.P. (Kathmandu University Journal of Science, Engineering and Technology, 2005)
Mathematical Modeling is that branch of Mathematics, which has application in all the fields, ranging from chemical engineering to bio-medical sciences. Here, mathematical modeling has been applied in a biomedical problem. Heat injuries are a common problem of south Asia. Burn injuries are severe cases of heat injuries, which cause serious damage to the skin and body and in severe cases may result in death. We have tried to estimate the extent of burn injuries with the help of mathematical modeling. This study has a great importance as fluctuations in various parameters affecting the burn injuries can be mathematically analyzed. This would help in curing the burn injuries as the extent of burn injuries could be found mathematically.